2021
DOI: 10.1021/acs.jpca.1c08627
|View full text |Cite
|
Sign up to set email alerts
|

Is Dissociation of HCl in DMSO Clusters Bistable?

Abstract: The dissociation of HCl embedded in DMSO clusters was investigated by projecting the solvent electric field along the HCl bond using B3LYP-D3/6-31+G(d) and MP2/6-31+G(d,p) levels of theory. A large number of distinct structures (about 1500) consisting of up to five DMSO molecules were considered in the present work for statistical reliability. The B3LYP-D3 calculations reveal that the dissociation of HCl embedded in DMSO clusters requires a critical electric field of 138 MV cm -1 along the H-Cl bond. However, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 40 publications
(94 reference statements)
0
12
0
Order By: Relevance
“…On the contrary, the electric field calculations using RI-MP2/cc-pVDZ level for both the RI-MP2/cc-pVDZ and M06-2X/cc-pVTZ optimized structures, the proton transfer is observed if the electric field along the O–H bond exceeds the critical electric field, without exceptions. The present set of results along with those of HCl-(DMSO) n clusters illustrate that the observed differences in estimating the critical electric fields using the MP2 and DFT (MO6–2X functional in the present case) methods does not originate from the structural factors of the cluster, but due to errors in calculating the molecular electrostatic potentials (MESP) using DFT methods. Thus, the limitations of DFT theory to appropriately model the proton-transfer reactions in terms of accurate description MESP can be attributed to the importance of HF exchange, which is generally under-represented in the exchange-correlation functionals due to energy fitting function with having a small (about 0.2) coefficient for the exchange energy …”
Section: Results and Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…On the contrary, the electric field calculations using RI-MP2/cc-pVDZ level for both the RI-MP2/cc-pVDZ and M06-2X/cc-pVTZ optimized structures, the proton transfer is observed if the electric field along the O–H bond exceeds the critical electric field, without exceptions. The present set of results along with those of HCl-(DMSO) n clusters illustrate that the observed differences in estimating the critical electric fields using the MP2 and DFT (MO6–2X functional in the present case) methods does not originate from the structural factors of the cluster, but due to errors in calculating the molecular electrostatic potentials (MESP) using DFT methods. Thus, the limitations of DFT theory to appropriately model the proton-transfer reactions in terms of accurate description MESP can be attributed to the importance of HF exchange, which is generally under-represented in the exchange-correlation functionals due to energy fitting function with having a small (about 0.2) coefficient for the exchange energy …”
Section: Results and Discussionmentioning
confidence: 62%
“…The reoptimization of the M06-2X/cc-pVTZ structures using RI-MP2/cc-pVDZ level reveals that, in general, the gross structure of the cluster remains unaltered with few exceptions, wherein four structures (5K, 8S, 6G, 6L, and 8S) which did not result in proton transfer at the M06-2X/cc-pVTZ level exhibit proton transfer at the RI-MP2 level of theory. In the case of the HCl-(DMSO) n clusters, it was shown that the electric field calculations using the MP2 method were comparable for the structures optimized using MP2 and DFT methods . Therefore, the proton-transfer process from phenol to ammonia is examined in terms of the electric field calculated at the RI-MP2/cc-pVDZ level along the O–H bond for the structures optimized using the RI-MP2/cc-pVDZ and M06-2X/cc-pVTZ methods, and the resulting plot of the O–H distances against the corresponding electric fields is shown in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, we anticipated that the extensive degree of charge reorganization in the cyclization transition state might be sensitive to the local electric field exerted by chloride. To assess the role of electric field effects quantitatively, we calculated the projection of the electric field induced by 1a ·Cl ‑ along the C–C bond-forming axis in the major pro -(S,R), minor pro -(R,S), and background transition states pictured in Figure A–C (Figure A) . While the major pro -(S,R) transition state experiences a positively applied field along this axis (0.136 V/Å), the minor pro -(R,S) and background transition states exhibit negative fields of increasing magnitude (−0.213 and −0.444 V/Å, respectively) (Figure A).…”
Section: Resultsmentioning
confidence: 57%